MEASURING THE QUALITY OF RICEFIELD WATER MANAGEMENT BASED UPON THE PERCEPTION OF FARMER’S WATER ASSOCIATION MEMBERS IN CENGKIR VILLAGE, BOJONEGORO DISTRICT EAST JAVA PROVINCE, INDONESIA - Purwanto, Wasis; Wijaya, I Nyoman Suluh; Usman, Fadly (Directorate of Research and Community Service (DRPM), 2024)
Cengkir village stands out as a promising area for agricultural land conservation within Bojonegoro Municipality. Consequently, planning and developing water irrigation infrastructure in Cengkir village has become crucial to supporting agricultural activities. However, practical implementation of water irrigation often encounters numerous obstacles, mainly due to mismanagement and insufficient community participation. Therefore, understanding the farmers' perspectives on management and identifying key factors influencing it are essential for further improvement. Cengkir village offers a compelling case for exploration in this regard. This research aims to investigate farmers' views regarding agricultural irrigation management within the Association of Water User Farmers (Himpunan Petani Pemakai Air - HIPPA) in Cengkir Village.Additionally, this study evaluates the relationship among factors influencing farmers' views on agricultural irrigation management. So, to understand the important factors from this perspective, this study employs the Likert Scale's weighting technique. The weighting technique is followed by a non-parametric Spearman Rank Correlation test to define the relationships among the variables and the influencing factors. The findings reveal that farmers' perceptions regarding irrigation management are at a standard level. Moreover, a high correlation exists among factors such as formal education level, motivation, needs, experience in rice cultivation, information knowledge, social environment, support from related departments, and land area, with the perspectives of HIPPA community members towards agricultural irrigation.